Prediction of Gaussian Volterra processes with compound Poisson jumps - Maleki Almani, Hamidreza; Shokrollahi, Foad; Sottinen, Tommi (Elsevier, 2024)
We consider a Gaussian Volterra process with compound Poisson jumps and derive its prediction law.
Keywords: Fractional Brownian motion; Gaussian Volterra process; Prediction law; Compound Poisson process; fi=Matematiikka|en=Mathematics|